Unprecedented High Oxygen Evolution Activity of Electrocatalysts Derived from Surface-Mounted Metal-Organic Frameworks - Li, Weijin; Watzele, Sebastian; El-Sayed, Hany A; Liang, Yunchang; Kieslich, Gregor; Bandarenka, Aliaksandr S; Rodewald, Katia; Rieger, Bernhard; Fischer, Roland A (Journal of the American Chemical Society, 2019)
The oxygen evolution reaction (OER) is a key process for renewable energy storage. However, developing non-noble metal OER electrocatalysts with high activity, long durability and scalability remains a major challenge. Herein, high OER activity and stability in alkaline solution were discovered for mixed nickel/cobalt hydroxide electrocatalysts, which were derived in one-step procedure from oriented surface-mounted metal-organic framework (SURMOF) thin films that had been directly grown layer-by-layer on macro- and microelectrode substrates. The obtained mass activity of ∼2.5 mA·μg at the defined overpotential of 300 mV is 1 order of magnitude higher than that of the benchmarked IrO electrocatalyst and at least 3.5 times higher than the mass activity of any state-of-the-art NiFe-, FeCoW-, or NiCo-based electrocatalysts reported in the literature. The excellent morphology of the SURMOF-derived ultrathin electrocatalyst coating led to a high exposure of the most active Ni- and Co-based sites.